From Drosophila development to adult: clues to Notch function in long-term memory - Zhang, Jiabin; Yin, Jerry; Wesley, Cedric S. (Frontiers in Cellular Neuroscience, 2013)
Notch is a cell surface receptor that is well known to mediate inter-cellular communication during animal development. Data in the field indicate that it is also involved in the formation of long-term memory (LTM) in the fully developed adults and in memory loss upon neurodegeneration. Our studies in the model organism Drosophila reveal that a non-canonical Notch-Protein Kinase C (PKC) activity that plays critical roles in embryonic development also regulates Cyclic-AMP Response Element Binding protein (CREB) during LTM formation in adults. Here we present a perspective on how the various known features of Notch function relate to LTM formation and how they might interface with elements of Wingless/Wnt signaling in this process.